Bowel dysfunction after elective spinal surgery: etiology, diagnostics and management based on the medical literature and experience in a university hospital - Jaber, Ayham; Hemmer, Stefan; Klotz, Rosa; Ferbert, Thomas; Hensel, Cornelia; Eisner, Christoph; Ryang, Y. M.; Obid, P.; Friedrich, Kilian; Pepke, Wojciech; Akbar, M. (Der Orthopäde, 2021)
Bowel dysfunction after spinal surgery is often underestimated and if not treated in a timely manner can lead to undesirable surgical interventions or fatal complications. The current medical literature primarily focuses on bowel dysfunction as a result of spinal injury.